Task integrity and task frequency in the L2 classroom - Lambert, Craig (2016)
This article provides a practical introduction to gaining maximum benefits from the repetition of tasks in the language classroom. The article is intended to complement Lambert, Kormos and Minn (2016) with a practitioner’s guide to tasks in language teaching. It begins with a discussion of the essential characteristics of tasks as pedagogic tools and the role that they play in L2 learning. This is followed by a discussion of the importance of task frequency in the learning process and how task repetition in the classroom might pose threats to the integrity of tasks as L2 learning tools. Finally, the last section discusses implementation strategies to ensure adequate task frequency while at the same time preserving task integrity, promoting optimum transfer of practice across tasks, and minimizing learner fatigue in repeating the same task multiple times. This section also discusses optional modifications to the basic approach to implementing tasks which can be used to optimize different aspects of learners’ performance across a task sequence. The article thus provides a practical basis for teachers to experiment with task-based language teaching in their own classrooms in order to determine what works best for their learners and in their educational contexts.